2014
DOI: 10.2478/s12175-014-0269-8
|View full text |Cite
|
Sign up to set email alerts
|

Subordination and superordination results associated with the generalized hypergeometric function

Abstract: ABSTRACT. In the present investigation, we obtain some subordination and superordination results involving Hadamard products for certain normalized analytic functions in the open unit disk. Relevant connections of the results, which are presented in this paper, with various other known results are also pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Motivated by the numerous allowances of the fractional derivative operators which have newly been reflected by many authors, here, we purposed two operators involving the generalized hypergeometric-type function and the generalized Beta function. Various studies can be found in [12,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by the numerous allowances of the fractional derivative operators which have newly been reflected by many authors, here, we purposed two operators involving the generalized hypergeometric-type function and the generalized Beta function. Various studies can be found in [12,13,14].…”
Section: Resultsmentioning
confidence: 99%
“….. Not much study was done using differential superordination theory on confluent hypergeometric function. Some superordination results were obtained for the generalized hypergeometric function as it can be seen in papers [9][10][11] some superordination results were stated in the form of sandwich-type theorems.…”
Section: Definition 3 ([3])mentioning
confidence: 99%
“…Magesh et al. ( 2014 ) studied the subordination and superordination results of the linear operator denoted by . Also, they discussed the sufficient condition to satisfy for some convex functions and with and and are analytic functions in with …”
Section: Introductionmentioning
confidence: 99%